If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -4 = 3y + 5 Reorder the terms: -4 + 4y = 3y + 5 Reorder the terms: -4 + 4y = 5 + 3y Solving -4 + 4y = 5 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -4 + 4y + -3y = 5 + 3y + -3y Combine like terms: 4y + -3y = 1y -4 + 1y = 5 + 3y + -3y Combine like terms: 3y + -3y = 0 -4 + 1y = 5 + 0 -4 + 1y = 5 Add '4' to each side of the equation. -4 + 4 + 1y = 5 + 4 Combine like terms: -4 + 4 = 0 0 + 1y = 5 + 4 1y = 5 + 4 Combine like terms: 5 + 4 = 9 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| -18=18(h-3) | | 12-26=8x+2 | | 118-97=35y-42y | | -X*2+16X=0 | | 61-5x=4x+15 | | 3x-7=154-4X | | -p=9 | | -30=-5(-2b) | | 8+16=5+91 | | 11-7x=143-35x | | 2r-11r=36 | | 0.9(8x+16)=1.4-(x+2) | | -51-2x=3x+24 | | -112-8x=7x+23 | | 125x^3-27= | | 6x^2+5x-25=0 | | 8y-21=5y | | 22x=15-48x^2 | | vx+w=3 | | -24=4x-8x^2 | | 140-4x=41x+15 | | -x^4-2x^2=0 | | 10+-7x=29+-14x | | 4(3x-3)=44 | | 3w^2-0.75w=0.5 | | 0.10x+0.5(6-x)=.10(6) | | 3(3y+1)=7(51-5y) | | 3(3y+1)=7(51+-5y) | | x+4y=3v | | 3(3y+1)=7(51-35y) | | 10+7x=29+14x | | 3(x+4)=5x-10 |